2011
DOI: 10.5458/jag.jag.jag-2010_026
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Rice Disproportionating Enzymes

Abstract: Disproportionating enzyme (D-enzyme) is a 4-αglucanotransferase (EC 2.4.1.25) that cleaves an α-1,4 glucosidic bond of α-1,4 glucan (donor molecule) and transfers the resulting glucan moiety to a non-reducing end of an acceptor molecule by creating a new α-1,4 glucosidic bond. D-enzymes have been identifi ed in a number of plant species and characterized most extensively in potato 1 7) and Arabidopsis, 8,9) but also studied in pea, 10) wheat, 11) germinating barley seed 12) and sweet potato tubers. 13) These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…We showed that DPE1 is expressed at a high level, specifically in rice endosperm, and that the activity of DPE1 is substantially high throughout starch accumulation and endosperm development. The temporal and spatial profiles of DPE1 transcripts were consistent with two previous reports (Ohdan et al, 2005;Akdogan et al, 2011). Furthermore, in wheat endosperm, the level of DPE1 was high at 5 to 10 DAF and higher in the later stages of seed development (Bresolin et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We showed that DPE1 is expressed at a high level, specifically in rice endosperm, and that the activity of DPE1 is substantially high throughout starch accumulation and endosperm development. The temporal and spatial profiles of DPE1 transcripts were consistent with two previous reports (Ohdan et al, 2005;Akdogan et al, 2011). Furthermore, in wheat endosperm, the level of DPE1 was high at 5 to 10 DAF and higher in the later stages of seed development (Bresolin et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The activity of DPE1 in transgenic rice seeds was further analyzed by its activity of releasing Glc from maltotriose (Akdogan et al, 2011). The OX and Ri lines tested exhibited significantly higher and lower DPE1 activities than did the wild type, respectively.…”
Section: Activity Of Dpe1 In Dpe1-overexpressed and -Suppressed Seedsmentioning
confidence: 99%
See 3 more Smart Citations